Factors associated with early treatment failure in adult hospitalized patients with community-acquired pneumonia - Vukadinović, Dubravka; Samardžić, Natalija; Janković, Slobodan; Tomić Smiljanić, Marijana; Pavlović, Radiša; Stefanović, Srđan (Vojnosanitetski pregled, 2017)
Background/Aim. Early treatment failure (ETF) in patients hospitalized for community-acquired pneumonia (CAP) is associated with prolonged hospitalization, increased risk of mortality and high treatment costs. The aim of this study was to analyze the relative importance of factors influencing ETF in hospitalized adult patients with CAP that are still insufficiently explored. Methods. A retrospective case-control study was carried out on a sample of 126 adult patients treated for serious CAP at the Clinic for Pulmonary Diseases, Clinical Center of Serbia, Belgrade, Serbia, during the 5-year period (2007–2011). The cases (n = 63) were consecutive patients with ETF, observed within the three days upon the admission to hospital, while the control group consisted of the equal number of randomly selected patients without such an outcome. The association between potential risk/protective factors and ETF was estimated using logistic regression analysis. Results. The coexistence of gastrointestinal disorders [adjusted odds ratio (OR) 18.83, 95% confidence interval (CI) 1.15–309.04], higher CURB-65 (C – confusion; U – urea 7 mmol/L; R – respiratory rate ≥ 30 breaths/min; B – systolic blood pressure < 90 mmHg or diastolic blood pressure ≤ 60 mmHg; 65 – age ≥ 65 years) score on admission (adjusted OR 2.57, 95%CI 1.05–6.25), initial use of nonsteroidal anti-inflammatory drugs (NSAIDs) in hospital (adjusted OR 38.19, 95%CI 3.61–404.51) and previous outpatient use of inhaled corticosteroids (adjusted OR 22.41, 95%CI 1.03–489.06) were found to be significant risk factors for ETF. On the other hand, older age and use of antibiotics before the hospitalization were associated with a significantly lower chance of experiencing ETF, reducing the odds for 98% and almost 90%, respectively. Conclusion. The avoidance of the routine in-hospital use of NSAIDs as well as the outpatient use of appropriate antibiotics may be beneficial for patients hospitalized for CAP in terms of reducing the risk of ETF. The CURB-65 score could be a better predictor of ETF than Pneumonia Severity Index. Further prospective studies are required to confirm these findings.
Keywords: pneumonia; hospitalization; treatment outcome; risk factors; comorbidity